GLOMERULAR FILTRATION RATE IN CHILDREN WITH ACUTE INTESTINAL INFECTIONS THAT OCCURRED WITH THE DEVELOPMENT OF TOXICOSIS WITH EXICOSIS - Галина Ивановна Выходцева; Евгения Юрьевна Киричек; Ольга Петровна Морозова; Людмила Ивановна Зиновьева; Ольга Ивановна Колесникова; Валерий Николаевич Сероклинов; Ирина Игоревна Мироненко (The Publishing House Medicine and Enlightenment, 2024)
The aim of the research - to evaluate the value of determining the calculated glomerular filtration rate (GFR) in children with acute intestinal infections (AII) with AII that occurred with the development of toxicosis with exicosis (TE) to assess the development of acute kidney injury. Materials and methods. The study included 135 children aged from 2 months to 6 years with clinical and laboratory manifestations of AII with TE. The study included 135 children aged from 2 months to 6 years with clinical and laboratory manifestations of AII with TE. Patients underwent BAC study with serum creatinine measurement by kinetic colorimetric test. As methods of GFR, the calculated GFR was determined using two formulas: by Schwartz G.J. formula (1976) and by the «bedside» Schwartz formula with a constant coefficient of 0.413. The results of the study. The comparative analysis of median values of estimated GFR calculated by the selected formulas showed that among children with AII with TE I degree in the age groups up to 1 year and from 1 to 3 years the level of the index was statistically significantly lower (p > 0.05). Among children with AII with TE of II degree in the age group up to 1 year of age the level of GFR was statistically significantly lower (p > 0,05). No statistically significant difference in median values and frequency of GFR decrease, calculated by the selected formulas, in children with AII with TE of I and II degree depending on the etiologic structure of AII was revealed. When determining the calculated GFR according to the «bedside» Schwartz formula, the index was registered statistically significantly lower and was decreased statistically significantly more often in children with AII I with TE of the I degree than when determining the calculated AII according to the Schwartz G.J. formula (1976). Conclusion. In children with AII a decrease in GFR was registered already at the development of TE of the first degree in the selected age groups. The change in GFR did not depend on the etiologic structure of AII.